A Marca Portugal - Cotrim, J. (2010)
Today’s systemic contours have a determining influence on the shaping of the Markets at a global scale, which, at the same time, ends up having dramatic implications on the re-making of strategic policies by governments aiming not to be defeated on the Battle of The Winners vs. The Losers. It is within this context, then, that a relatively new concept has been emerging as a necessary key instrument for modern nations to face the contemporaneous needs and challenges of today’s globalized world – the Country-Brand. Thus, this dissertation was object of thought, study, investigation, research and subsequently presentation as an attempt to show and give a complete glance over the already undisputable certainty that the Country-Brand is indeed a determining factor in the gaining of competiveness of nations worldwide. And, in the case of Portugal, this certainty is more obvious than ever. In the next pages, I will try to present in the most possible incisive way the various contours associated to this problematic. The structure, the chapters and content of this work were carefully thought and chosen in order to give a consistent and complete sight and diagnostic of the Portuguese reality in relation to phenomena such as Globalization, subsequent increasing of competiveness among nations, but, mainly, in relation to how Portugal perceives itself when facing one of the most determinant features of today’s Global Village – the rising value of the Country-Brand. Briefly, and in a much comprehensive manner, this of piece of work aims to put under discussion the great challenges that the management of the Brand of Portugal may face in the coming future, as well as, the consequently competiveness of the Portuguese business agents in the international scene.